2020
DOI: 10.1016/j.annonc.2020.08.1701
|View full text |Cite
|
Sign up to set email alerts
|

1387P Phase Ib study of LXH254 + LTT462 in patients with KRAS- or BRAF-mutant NSCLC

Abstract: Background: Tumor tissue has a complex structure, which includes different cellular and matrix components. Ex vivo tissue explants retain individual features of original neoplasms and may be used for personalized testing of the drug sensitivity. The existing morphological methods for evaluation of drug response in alive tissue sections are extraordinarily time-consuming and have poor interlaboratory reproducibility. We attempted to establish RNA-based expression assays, which may supplement or replace the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Some resistance mechanisms may be overcome by novel multi-RAF and downstream ERK1/2 inhibitors, like LXH254 and LTT462, which are in early phase trials for BRAF or KRAS mutant NSCLC [ 188 ]. VS-6766 is one such RAF/MEK clamp that is being studied in BRAF mutant NSCLC (RAMP 202 NCT).…”
Section: Ros1mentioning
confidence: 99%
“…Some resistance mechanisms may be overcome by novel multi-RAF and downstream ERK1/2 inhibitors, like LXH254 and LTT462, which are in early phase trials for BRAF or KRAS mutant NSCLC [ 188 ]. VS-6766 is one such RAF/MEK clamp that is being studied in BRAF mutant NSCLC (RAMP 202 NCT).…”
Section: Ros1mentioning
confidence: 99%
“…For example, trials for the combination of LXH254 with LTT462 or trametinib (Table 1 ) are currently active but not recruiting NSCLC and melanoma patients (NCT02974725 and NCT04417621). In the former, a good safety profile and preliminary efficacy were observed in BRAF mutants [ 142 ], while in the latter, the combination with LTT462 or trametinib appears to be promising in NRAS‐mutant melanoma patients [ 143 ]. These findings provide new hope for RAS mutant patients; however, it is unclear whether these approaches can be applied to all scenarios where the signaling is dependent on dimerization (e.g., class II or III BRAF mutants).…”
Section: Strategies To Overcome the Limitationsmentioning
confidence: 99%
“…This study further confirmed the survival advantage of dabrafenib plus trametinib combination compared to single agents. Furthermore, LXH254, a novel BRAF/CRAF inhibitor, plus LTT462, an ERK1/2 inhibitor, was explored to evaluate its activity in patients with advanced/metastatic K-ras- or BRAF -mutant NSCLC in a phase Ib dose escalation study; preliminary analysis showed signs of efficacy in patients with BRAF -mutant NSCLC ( 78 ). Dose expansion is ongoing, and further efficacy analysis remains to be seen.…”
Section: Current Treatment Landscapementioning
confidence: 99%
“…These reports revealed that RAS gene might a critical gene modulator in resistance mechanisms to BRAF/MEK inhibitors. The last European Society For Medical Oncology (ESMO) congress reported a novel combination of LXH254 and LTT462 that might overcome RAS-related resistance to BRAF/MEK inhibitors ( 78 ). This regimen has shown antitumor activity in BRAF -mutant and K-ras -mutated patients.…”
Section: Current Treatment Landscapementioning
confidence: 99%